2007
DOI: 10.1111/j.1365-2222.2007.02906.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the epithelial inflammatory response to rhinovirus in an atopic environment

Abstract: Under the influence of an atopic environment, the epithelial inflammatory response to RV is down-regulated, associated with increased viral proliferation and augmented cell damage, while TGF is up-regulated. These changes may help explain the propensity of atopic asthmatic individuals to develop lower airway symptoms after respiratory infections and indicate a mechanism through which viral infections may promote airway remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 41 publications
4
62
1
7
Order By: Relevance
“…Similar responses were observed for other profibrotic factors, such as transforming growth factor-b [90] and fibroblast growth factor 2 [93]. These data indicate a mechanism through which viral respiratory infections may promote airway remodelling and the chronic asthma phenotype in atopic asthmatic individuals.…”
Section: Mechanisms Of Virus-induced Exacerbationsupporting
confidence: 60%
See 1 more Smart Citation
“…Similar responses were observed for other profibrotic factors, such as transforming growth factor-b [90] and fibroblast growth factor 2 [93]. These data indicate a mechanism through which viral respiratory infections may promote airway remodelling and the chronic asthma phenotype in atopic asthmatic individuals.…”
Section: Mechanisms Of Virus-induced Exacerbationsupporting
confidence: 60%
“…In line with these observations, it has been shown that, under the influence of an atopic immune response, the epithelial inflammatory response to RV becomes suboptimal with respect to cytokines and chemokines, such as IL-6, IL-8 and RANTES. Such a response is associated with inadequate viral clearance and increased RV-induced cytotoxicity [90]. However, the timing of the infection might play a significant role, since simultaneous infection and allergen exposure significantly increase the severity of asthma exacerbations in asthmatics, whereas allergen exposure prior to infection has minimal or no effect on symptoms or airway hyperresponsivess [33,91].…”
Section: Mechanisms Of Virus-induced Exacerbationmentioning
confidence: 99%
“…Using PBMC-derived plasmacytoid dendritic cells it was further shown that: 1) the surface expression of the high-affinity IgE receptor FcεRI was higher in allergic asthmatic children, compared with nonallergic nonasthmatic controls; 2) IFN-α and IFN-λ1 production in response to HRV was inversely associated with the intensity of the FcεRI expression on plasmacytoid dendritic cells; and 3) after FcεRI cross-linking with rabbit anti-human IgE, allergic asthmatic children had significantly lower HRV-induced IFN responses than allergic nonasthmatic controls [112]. Moreover, in vitro exposure of human BECs to HRV revealed that under the influence of an atopic environment the inflammatory response to the virus was downregulated, viral proliferation was increased and virus-induced cell damage was augmented [110]. A deficient innate immune response to HRV infection was demonstrated on atopic asthmatic BEC primary cultures that were characterised by a profound impairment of virus-induced IFN-β production, impaired epithelial cell apoptosis and increased virus replication [113].…”
Section: Allergic Sensitisation Asthma and Hrv Infectionmentioning
confidence: 95%
“…4) [110]. Hence the nature of immune responses to HRV differs between atopic asthmatic and normal subjects, which is characterised by a deficient production of IFN-γ and IL-12 by PBMC in atopic asthmatics [111].…”
Section: Allergic Sensitisation Asthma and Hrv Infectionmentioning
confidence: 99%
“…Боль-шой интерес вызвало сообщение M. Xatzipsalti и со-авт. о том, что антигены риновируса обнаруживаются в крови госпитализированных по поводу обострения бронхиальной астмы спустя 6 нед после инфекции [3]. М. Wos и соавт.…”
unclassified